Fundamentals of character building in drama Iraqi TV (Journal of the College of Basic Education, 2023)
The personality is a main axis on which the drama is based, as the tributary that moves fromIts path is the event and the dramatic conflict; The personality also took center stage in the studiesPsychological, social, literature and drama studies. Besides, personality is one of the valuesThe drama on which the maker of the artwork relies in the process of employing it within the visual work.With the rest of the elements of the dramatic construction in order to serve as a focal point in the construction of the event and therefore we findThe dramatic work maker pays great attention in his interpretation of the dramatic character according to a constructive treatmentThe dramatic character and its interaction with the rest of the elements according to a vision characterized by innovation in character buildingDramatism within the visual performer, therefore, many interpretations have been developed to understand the componentsThe dramatic character and its construction within the visual achievement.The research problem and the need for it:The Iraqi TV drama witnessed a wide development in the technical and artistic fieldsIt has become a field adjacent to current scientific and technical concepts, rather than at the level of treatmentDirective only, the new writing of the television script has undergone multiple openingsIt resulted in a lot of new experiences, and it formed the character in the TV dramaContemporary is an active "axis" in the processes of building the audiovisual image by focusing on itThe dramatic act affecting the recipient; Through its transformations, growth and continuous development 0It is her actions and behavior that generate the impression of her, and through her, she becomes active and influentialIts goal that it seeks to achieve, the personality is built through the consolidation of a group of foundationsDramatic, social and psychological on the one hand, and ways to treat it on television on the one hand